Analisis Dan Peningkatan Pengalaman Pengguna Pada Platform Sepulsa Menggunakan Metode Use Centered Design (UCD) - Rahayu, Yari Ardiansyah; Kalimat, Arul Budi; Sumarna, Ertansyah Rizal Priadi; Suparman, Tegar Radiansyah; Hestiyanti, Mita; Rahayu, Asri Nurjati; Nurhayati, Mila; Ramdhani, Nabila Aprilia (Jurnal Teknologi Informasi, 2025)
Sepulsa.com, is a website that provides credit top-up services, purchasing game vouchers, and variousother financial transactions. The importance of usability on sepulsa.com goes beyond just practicalconsiderations as it reflects the real challenges in delivering a satisfying user experience. The methodused in this research is user centered design. This aims to ensure that the UI/UX design of the productor system meets user needs, reduces errors, increases efficiency, and reduces development costs. Thisresearch evaluates the register, login and purchase game voucher features using the system usabilityscale (SUS). Initial evaluation results show an average score below 68, indicating a usability problemthat requires improvement. However, further analysis shows that focusing on improving the gamevoucher access feature and adjustments to register and login can increase the evaluation score into aJuTI “Jurnal Teknologi Informasi”Fakultas Teknologi InformasiUniversitas Teknologi Digital Indonesia (d.h STMIK AKAKOM)DOI: 10.26798/juti.v1i2.xxx vol.1, No.2, Februari, e-ISSN: 2962-4118better category according to the system usability scale (SUS), reaching an average score for login of71,625, classified as "good" with a grade scale of c.Keywords: Usability, UI/UX, Sepulsa, User Centered Design, System Usability Scale